Η Σαφράμπολη της Μικράς Ασίας και το πρόβλημα του ονόματος της κατά τη βυζαντινή περίοδο - Αρτόπουλος Ιωάννης Γ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2004)
Saframpoli (Saframbolu today) is a town located in Paphlagonia in northern Asia Minor. It was populated by Greeks and Ottoman Turks until the last century. The written history of Saframpolu dates back to the 14th century A. D. The Greeks claim the name of the town in the Byzantine period was Theodoroupolis, though it never appears in the literature of the region. One can find in the town various monuments of the Hellenistic period that indicate the existence of an important city in the region. In particular, the still existing epigraph on the door of the Christian Orthodox Church dedicated to protomartyr Hagios Stefanos indicates the church was built by Empress Eudokia Athinais in the early Byzantine era (5th century A. D.). One of the stories that survives until nowadays among the Greek people of Saframpolu is that of the capture of the town by the Ottoman Turks. This story has many similarities to the description of the capture of Dadybra by the Turks in the second half of the 12th century, given by Nikitas Choniates. Seals (molybdobula) from the 10th century bearing the picture of Hagios Stefanos and the names of the bishops of Dadybra indicate that the latter was the ancient Saframbolu, the only town in the region having an old church dedicated to the aforementioned saint.